2012
DOI: 10.1111/j.1600-0722.2011.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment experience, frequency of dental visits, and children’s dental fear: a cognitive approach

Abstract: Cognitive elements play a key role in dental anxiety. Nevertheless, relatively little is known about how dental treatments and frequency of visits to the dentist are related to dental fear and its cognitive antecedents. This study aimed to explore the relationships between dental visits, past treatment experiences, expectations on the aversiveness/probability of negative dental events, and dental fear in children. The participants were 147 children (60% female; mean age = 12.0 yr) who completed a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 29 publications
(70 reference statements)
6
34
1
5
Order By: Relevance
“…DA is believed to be associated with situations in which there was an experience of pain or the needing of more invasive treatment, such as an extraction. The fact that dental care resolves this symptom does not lead to higher levels of DA . reported that children who have only undergone restorations in their lives are less anxious, while those who have been submitted to extractions tend to react with higher levels of DA during subsequent treatment sessions.…”
Section: Discussioncontrasting
confidence: 65%
“…DA is believed to be associated with situations in which there was an experience of pain or the needing of more invasive treatment, such as an extraction. The fact that dental care resolves this symptom does not lead to higher levels of DA . reported that children who have only undergone restorations in their lives are less anxious, while those who have been submitted to extractions tend to react with higher levels of DA during subsequent treatment sessions.…”
Section: Discussioncontrasting
confidence: 65%
“…Even though there is no clear evidence in relation to the effectiveness of dental fillings for the treatment of caries in the primary dentition [Yengopal et al, 2009;Marshman et al, 2012], we could speculate that restoration may reduce the occurrence of dental pain. Nevertheless, having received dental fillings was associated with the perceived probability of negative dental events and as a consequence could increase dental fear levels [Carrillo-Díaz et al, 2012]. Indeed the prevention of caries occurrence would be more effective to reduce dental fear levels, since the strong association found in the present study was between caries and dental fear.…”
Section: Discussionmentioning
confidence: 45%
“…Moreover, dental fear represents a barrier for accessing dental services and treatments, which may lead to a worsening of one's oral status. Indeed, those children with higher levels of dental fear appear to visit the dentist less frequently and miss appointments . Furthermore, dental fear in children and adolescents is a widespread problem, with an estimated prevalence of between 5.7% and 19.5% .…”
mentioning
confidence: 99%